Factors associated with peer aggression (Bullying): Results of a population study in Peru: Agresión entre pares (Bullying) - Valle, Rubén (2022)
Background: Peer aggression (Bullying) is a frequent problem in the school-age population, whose occurrence is determined by factors from different contexts, and not only from the school. Objective: To determine the annual prevalence of peer aggression among secondary school students in Peru, in its forms of aggression, victimization and aggression-victimization; and to determine the individual, family and community factors associated with peer aggression based on the ecological model of violence. Material and methods: Secondary analysis of the database of the "IV National Study on Drug Prevention and Consumption in High School Students 2012". Data from 48 025 secondary school students were analyzed taking into account the two-stage, stratified probability sampling of the original study. The dependent variable peer aggression was studied for each of its components: aggression, victimization and aggression-victimization. Results: 48% of students reported having participated in acts of peer aggression in the period of one year (aggression: 10.5%, 95%CI: 9.9-11.1; victimization: 15.8%, 95%CI: 15.2-16.4; and aggression-victimization: 21.7%, 95%CI: 20.6-22.9). Variables from the individual and community spheres were associated with aggression, victimization, and aggression-victimization. Conclusions: The prevalence of peer aggression in Peru is high, with the most frequent group being aggression-victimization. Different individual and community factors influence peer aggression. Intervention programs on peer aggression in Peru should have a preventive, multilevel and multidisciplinary approach to address all aspects of the problem.